HARMONIZING ISLAMIC ECONOMIC LAW WITH COMMON LAW IN AUSTRALIA: A COMPARATIVE LEGAL ANALYSIS - Sarah Taylor; Thomas Mitchell; Zoe Johnson (Sharia Oikonomia Law Journal, 2025)
The increasing presence of Muslim communities and the growing interest in ethical finance have sparked debates over the integration of Islamic economic principles within secular legal systems, particularly in Western common law jurisdictions such as Australia. Despite Australia’s multicultural legal ethos and openness to financial innovation, Islamic economic law—particularly in areas such as profit-sharing, interest prohibition, and zakat-based finance—faces challenges related to enforceability, recognition, and legal compatibility. This study aims to explore the extent to which Islamic economic principles can be harmonized with Australian common law, without undermining the secular character of its legal system. Employing a comparative legal methodology, the research analyzes statutory and case law frameworks in Australia alongside primary Islamic legal sources and interpretive jurisprudence (fiqh muamalat). The findings reveal areas of convergence in contract law, trust structures, and ethical investment, but also identify conflicts in areas such as riba, gharar, and dispute resolution. The study concludes that partial harmonization is feasible through legal pluralism and regulatory accommodation, particularly in the domain of commercial transactions. The research contributes to ongoing discussions on legal inclusivity, multicultural jurisprudence, and the future of Islamic finance in Western legal systems.